Cost-effectiveness analysis for sustainable wastewater engineering : a case study at Minho-Lima’s rivers basins (Portugal) - Costa, Sérgio (2007)
The present work was focused on a methodological assessment for defining cost-effective measures regarding to wastewater sanitation in rural areas and was carried out within the project AQUA Project – Preliminary Studies for the Water Framework Directive Implementation at the Minho and Lima’s Rivers Basins. In order to assure a good ecological and chemical status in water bodies according to Water Framework Directive, a set of priority and complementary actions combined with a cost-effectiveness analysis was used to select a wastewater treatment strategy to increase public attendance. Using geoprocessing methodologies and geographic information multicriteria analysis (e.g.: soil, land use, topography), locations with high potential for implementation of low-energy wastewater treatment systems were identified and worked out with cost-functions. The results show that a combination of centralized and decentralized plants allow a cost-effectiveness attendance of 1,51 k¤/equivalent inhabitant in Minho and Lima’s river basins. The approach indicates that low-energy wastewater treatment plants are interesting options with a promising cost-effectiveness potential in rural areas.